Changing Ideas and Contours of Entrepreneurship in the History of Thought: On the Fluidity and Indefiniteness of a Term - Bögenhold, Dieter (Senate Hall, 2019)
Not only in the history of economic theory are changing conceptions and definitions of entrepreneurship on the agenda but also current entrepreneurship research shows oscillating contours in the semantic use of the word. The paper takes this notion as a backdrop, endeavouring to differentiate and spell out different relationships between entrepreneurship and self-employment. In some cases, entrepreneurship and self-employment have a one-to-one fit and can be used interchangeably while in other cases, entrepreneurship does not correspond to the labour market category of self-employment or, vice versa, self-employment as practised in reality does not match entrepreneurship empirically. Freelancers working part-time or full-time, farmers, micro-entrepreneurs without employees, and 'big' entrepreneurs employing a larger number of wage- or salary-dependent employees are difficult to summarize in one single box. The intention of this paper is to provide an introduction to the different semantics and to highlight and explain difficulties that arise when talking about entrepreneurship in order to systematize competing and hazy interpretations. The general discussion attempts to combine an explanation in economics, which is rather economically-functionally oriented, with an explanation with a sociological-institutional focus, which is oriented more in terms of social rationalities, biographies and various other dimensions.
Keywords: entrepreneurship|history of economic thought|competition|Adam Smith|Joseph A. Schumpeter|Israel Kirzner